Attraktiva utomhusmiljöer: ett undersökande arbete om att förlägga delar av arbetsdagen utomhus - Axell, Elin; Celegin, Helena (My University, 2021)
This bachelor thesis has been conducted at the life science company GoCo Health Innovation City with the purpose of examining sustainable ways to create outdoor office environments. Exposure to the outdoors and to nature is correlated with better health values and promotes a stronger immune system and reduces stress. To identify the needs of the future users, qualitative and quantitative user studies were conducted. Furthermore, market research of already existing concepts was researched and evaluated. These studies resulted in a list of demands for the future concept. Thereafter, the phase of idea generation was initiated where the usage of several different methods resulted in a variety of solutions. These solutions were then evaluated through established evaluation matrices which resulted in the selection of three concepts to be developed further. The finished result were three different outdoor office concepts with different usage options to ensure that they together fulfil the list of demands. Further research should explore ways of creating even more direct contact with nature elements as well as include a thorough ergonomic evaluation of the concept, with the goal to offer the user the best possible experience.
Keywords: Utomhuskontor, Utomhusmiljöer, Arbetsmiljö, Utomhusvistelse